Caffeine Enhances the Calcium-Dependent Cardiac Mitochondrial Permeability Transition: Relevance for Caffeine Toxicity - Sardão, Vilma A. (2002)
Caffeine (1,3,7-trimethylxanthine), a compound present in beverages such as tea and coffee, is known to be toxic at high concentrations. Some of the observed clinical conditions include cardiovascular disease and reproductive disorders, among others. The possible toxic effects of caffeine on heart mitochondria are still poorly understood. The influence of caffeine on the mitochondrial permeability transition has not been clarified so far. The objective of this study was to investigate whether caffeine, at toxic concentrations, had any stimulating effect on the permeability transition of heart mitochondria isolated from Wistar rats, as well as whether it influenced mitochondrial respiratory parameters. Our results show that caffeine reduced mitochondrial ability to accumulate calcium by increasing the susceptibility of heart mitochondria to the opening of the transition pore. Caffeine not only hindered mitochondrial capacity to recover membrane potential after calcium addition but also increased the rate of calcium-dependent mitochondrial swelling and calcium-induced calcium release. The increased swelling was also observed in nonenergized mitochondria. Caffeine also showed a complex array of effects on heart mitochondrial bioenergetics, as evaluated by respiratory parameter measurements. We observed an increase in state 4 respiration and a depression in state 3 respiration, although no effect was observed on succinate-sustained mitochondrial membrane potential in the absence of calcium. Our work may be relevant to cardiovascular problems linked to caffeine toxicity and also to in vitro experiences involving caffeine-induced calcium release from the sarcoplasmic reticulum and uptake by mitochondria.